2022
DOI: 10.1044/2021_aja-21-00133
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Noise Exposure on the Middle Ear Muscle Reflex in a Veteran Population

Abstract: Purpose: Human studies of noise-induced cochlear synaptopathy using physiological indicators identified in animal models (auditory brainstem response [ABR] Wave I amplitude, envelope following response [EFR], and middle ear muscle reflex [MEMR]) have yielded mixed findings. Differences in the population studied may have contributed to the differing results. For example, due to differences in the intensity level of the noise exposure, noise-induced synaptopathy may be easier to detect in a military … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 69 publications
(97 reference statements)
2
17
0
4
Order By: Relevance
“…It is not surprising that a firearm user who uses HPDs “less than half the time” exhibits cochlear pathology (inferred from the decreased DPOAE amplitudes). Because of the potential for combined cochlear and neural pathologies, Bramhall et al (2022) recently used a computational model to re-evaluate the data from Bramhall et al (2017) and predict synaptopathic loss based on both the measured ABR and DPOAE responses ( Bramhall et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not surprising that a firearm user who uses HPDs “less than half the time” exhibits cochlear pathology (inferred from the decreased DPOAE amplitudes). Because of the potential for combined cochlear and neural pathologies, Bramhall et al (2022) recently used a computational model to re-evaluate the data from Bramhall et al (2017) and predict synaptopathic loss based on both the measured ABR and DPOAE responses ( Bramhall et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are significant uncertainties surrounding the precision of historical noise exposure estimates generated via survey data, which are a consequence of both errors in recall and lack of individual sound exposure level information. Therefore, more recent approaches have included the exploration of hearing-in-noise function (performance) for possible associations with measures of OHC function (typically assessed using DPOAEs) and/or measures of neural function using evoked potentials, such as the auditory brainstem response (ABR), acoustic reflex threshold/middle ear muscle reflex (MEMR), or envelope following response (EFR) (Grant et al, 2020;Mepani et al, 2020Mepani et al, , 2021Parker, 2020; 10.3389/fnins.2022.1005148 Shehorn et al, 2020;Bramhall et al, 2022). At present, the audiogram remains the gold standard clinical tool in audiology (for recent review see Le Prell et al, 2022), but there is universal agreement that clinical dysfunction can be "hidden" beyond a normal audiogram (i.e., "hidden hearing loss"; see Schaette and McAlpine, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Shehorn et al ( 2020 ) reported that high lifetime noise exposure is associated with lower ipsilateral broadband MEMR amplitude in normal-hearing young and middle-aged adults. Recently, Bramhall et al ( 2022 ) measured the contralateral MEMR growth functions in 92 audiometrically-normal military veterans (who are typically exposed to firearm noise) and non-veterans aged 19–35 using a wideband probe and a broadband elicitor. The authors reported a trend of reduced MEMR growth functions in military veterans with high noise exposure compared to their non-veteran control counterparts.…”
Section: Objective Proxy Measures Of Cochlear Synaptopathymentioning
confidence: 99%
“…We acknowledge the limitations imposed by the small sample size in the present study but note that focusing on a novel cohort of participants with asymmetric peripheral neural status helped to limit idiosyncratic factors in the psychoacoustic and electrophysiologic data. We also note that while we focused on a previously validated measure of eCND and its published participant cohort ( Mepani et al , 2020 ), it is possible that more recently developed estimates of eCND ( Bramhall et al , 2022 ; Mepani et al , 2021 ) could better account for variation in perceptual auditory hypersensitivity. Future work will aim to objectively dissociate between complaints of loudness discomfort and affective sound processing at multiple stages of the central auditory pathway and in individuals with heterogeneous hypersensitivity phenotypes.…”
Section: Discussionmentioning
confidence: 99%